Linseed improvement in oil and fibre quality - Kaur, Vikender; Yadav, Rashmi (Indian Farming, 2018)
Flax oil is widely recognized for its probiotic properties having beneficial effects on coronary heart disease, neurological and hormonal disorders, colon tumor, breast cancer and atherosclerosis. Because of various health benefits, the demand for whole and milled-flax seed, and cold pressed flaxseed oil is increasing; where seeds and oil are being used for fortification of food products as a health benefit ingredient. Hence, the interest in linseed is rejuvenating in present era. The narrow genetic base used for the development of linseed cultivars, scarce availability of related species to incorporate new variation, lack of hybrid production systems and the limited molecular breeding have hampered yield and quality improvements, limiting linseedcompetitiveness. To improve economic value of linseed, varietieswith fatty acid profile tailored to specific need, good meal and fiberquality, high yield and stress tolerance are needed. The whole genome sequence achieved in 2012 is enabling more detailed study of the genes and diversity in commercially important accessions of linseed. Further research is important for adapting linseed cultivation to changing environmental conditions or to changing market needs as well as its continued improvement into a truly multi-purpose crop.